First person - Malabika Chakrabarti (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Malabika Chakrabarti is first author on 'Targeted repression of Plasmodium apicortin by host microRNA impairs malaria parasite growth and invasion', published in DMM. Malabika is a PhD student in the lab of Dr Shailja Singh at Jawaharlal Nehru University, New Delhi, India, investigating the functional roles of human microRNA in the pathogenicity of the malaria parasite.